Financial Report Digitalization on Transparency and Accuracy in Multinational Companies - Tyahya Whisnu Hendratni (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The digital transformation of financial reporting has become essential for multinational companies to ensure transparent and accurate financial information in the Industry 4.0 era. This study aims to examine the influence of financial report digitalization on the transparency and accuracy of financial information in multinational companies. A quantitative approach was employed, using Structural Equation Modeling to analyze data from 162 multinational companies selected through purposive sampling. Data were collected via questionnaires distributed to finance division heads and supplemented by annual reports. The findings reveal that digitalization significantly enhances transparency (path coefficient 0.632, p-value less than 0.001) and accuracy (path coefficient 0.571, p-value less than 0.001), driven by technologies such as enterprise resource planning, cloud accounting, blockchain, and artificial intelligence. This study concludes that digitalization strengthens financial governance by improving data accessibility and reliability, though its applicability may be limited to companies with advanced digital infrastructure. These results provide insights for companies to invest in digital technologies and for regulators to develop harmonized reporting standards.